2020
DOI: 10.1128/msphere.00898-20
|View full text |Cite
|
Sign up to set email alerts
|

Discovering the Molecular Determinants of Phaeobacter inhibens Susceptibility to Phaeobacter Phage MD18

Abstract: Bacteriophages have immense potential as antibiotic therapies and in genetic engineering. Understanding the mechanisms that bacteriophages implement to infect their hosts will allow researchers to manipulate these systems and adapt them to specific bacterial targets. In this study, we isolated a bacteriophage capable of infecting the marine alphaproteobacterium Phaeobacter inhibens and determined its mechanism of infection. Phaeobacter virus MD18, a novel species of bacteriophage isolated in Woods Hole, MA, ex… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…TEM analysis revealed that phage vB_EliS-L02 was a siphovirus, the diameter of the long prolate head was 159.4 ± 4.4 nm, and the length of the tail was 240.0 ± 5.1 nm ( Figure 1A ). The morphology of phage vB_EliS-L02 was remarkably distinct from the only reported Erythrobacter phage vB_EliS-R6L (Lu et al, 2017 ), and it is similar to a few Cbk-like phages, namely, Roseobacter phage DSS3P8 (Zhan et al, 2016 ), Phaeobacter phage MD18 (Urtecho et al, 2020 ), Caulobacter phiCbk-like phage (Gill et al, 2012 ), and Sphingobium phage Lacusarx (Nielsen et al, 2017 ).…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…TEM analysis revealed that phage vB_EliS-L02 was a siphovirus, the diameter of the long prolate head was 159.4 ± 4.4 nm, and the length of the tail was 240.0 ± 5.1 nm ( Figure 1A ). The morphology of phage vB_EliS-L02 was remarkably distinct from the only reported Erythrobacter phage vB_EliS-R6L (Lu et al, 2017 ), and it is similar to a few Cbk-like phages, namely, Roseobacter phage DSS3P8 (Zhan et al, 2016 ), Phaeobacter phage MD18 (Urtecho et al, 2020 ), Caulobacter phiCbk-like phage (Gill et al, 2012 ), and Sphingobium phage Lacusarx (Nielsen et al, 2017 ).…”
Section: Resultsmentioning
confidence: 86%
“…Results of phylogenetic trees based on MCP and portal protein showed that Sphingobium phage Lacusarx was the only phage clustered together with phage vB_EliS-L02. And, these two phages were clustered with some Roseobacter phages according to the phylogenetic tree of portal protein, suggesting a relatively close evolutionary distance among them (Zhan et al, 2016 ; Urtecho et al, 2020 ). Moreover, the evolutionary relationships, based on phoH among vB_EliS-R6L, other viruses, and their hosts, revealed that phage vB_EliS-L02 formed a distinctly separate cluster, with the closest relationship with Sphingobium phage Lacusarx.…”
Section: Resultsmentioning
confidence: 99%
“…Overall, owing to putative attP mutations and recombination, the probability of establishing lysogeny for these phages may be greatly reduced or lost. For example, the CbK‐like phage MD18 was shown to inhibit host growth in liquid culture at a concentration below the plaquing detection limit (200 PFU/mL) (Urtecho et al, 2020).…”
Section: Resultsmentioning
confidence: 99%